Internalization of Community Empowerment High Value in MSI Community - Naredia, Shubuha Pilar; Supriyanto, Supriyanto (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
Community empowerment, as mentioned in SDGs, nowadays becomes trend activity in the social world stage. Mentari Sehat Indonesia (MSI) implements a community empowerment practice based on noble values. Many internalization stages have been taken to maintain the existence of those values. This research aims to describe noble values existing in MSI community in community empowerment practice along with its internalization stages using universal noble value category developed by Kluckhohn. This research is a single case study with data sourcing from informant, library study, written document and archive, and visual data collected through interview, observation and documentation. Informant was selected purposively based on sex, leadership for regional subsidiary organization, and education level. Data was analyzed using an interactive model of analysis including data reduction, data display, and conclusion drawing as well as verification. Data validation was conducted using source triangulation technique. The research found various noble values existing in MSI Community:   nature of life, nature of work, and work ethos, relation between human and nature, perception on time, and relation between humans and their fellows. The internalization of noble values was conducted by MSI community through value transformation, value transaction, and trans-internalization stages